Dermatofibroma Arising within a Black Tattoo. (23rd September 2014) - Lobato-Berezo, Alejandro; Churruca-Grijelmo, Micaela; Martínez-Pérez, Marcela; Imbernón-Moya, Adrián; Vargas-Laguna, María Elena; Fernández-Cogolludo, Eva; Aguilar-Martínez, Antonio; Gallego-Valdés, Miguel Ángel
Abstract : Many complications have been reported over tattoos, some of which are tumours, such as dermatofibromas. It is important to establish a differential diagnosis because they can resemble other malignant lesions as dermatofibrosarcoma protuberans. We report the development of a dermatofibroma in a 21-year-old man with a tattoo painted two years ago.